Clinically-evident Tophi Are Associated With Reduced Muscle Force in the Foot and Ankle in People With Gout: A Cross-sectional Study - Stewart, S; Dalbeth, N; Otter, S; Gow, P; Kumar, S; Rome, K (BioMed Central, 2017)
Background: The foot and ankle represent a common site for tophi in people with gout, yet it is unclear whether the presence of tophi is related to impaired muscle function. This study aimed to determine the association between foot and ankle tophi and muscle force in people with gout. Methods: Participants with gout were stratified into two groups based on the presence of clinically-evident tophi affecting the foot or ankle on physical examination. Isometric muscle force for plantarflexion, dorsiflexion, inversion and eversion was measured using static dynamometry. Mixed-models regression was used to determine the difference in muscle force between the two groups while adjusting for age, disease duration and foot pain. This model was also used to determine the difference in muscle force between presence and absence of tophi at specific locations within the foot and ankle. In addition, Pearson’s correlations were used to determine the association between total foot tophus count and muscle force. Results: Fifty-seven participants were included (22 with foot or ankle tophi and 35 without foot or ankle tophi). Foot and ankle tophi were most often seen at the Achilles tendon. After adjusting for age, disease duration and foot pain, participants with tophi had significantly reduced muscle force during plantarflexion (P < 0.001), dorsiflexion (P = 0.003), inversion (P = 0.003) and eversion (P = 0.001) when compared to participants without tophi. Those with Achilles tophi had significantly reduced force during plantarflexion (P < 0.001), inversion (P = 0.008) and eversion (P = 0.001). No significant differences in muscle force were observed between the presence and absence of tophi at other foot or ankle locations. There were also no significant correlations between total foot tophus count and muscle force (all P > 0.05). Conclusion: In people with gout, clinically-evident foot or ankle tophi are associated with muscle force deficits during foot plantarflexion, dorsiflexion, inversion and eversion, which persist despite adjusting for age, disease duration and foot pain. Tophi at the Achilles tendon, which associate with force deficits, may contribute to reduced muscular activation and consequent disuse muscle atrophy.
Keywords: Gout; Foot; Dynamometry